EFFECTS OF ETHANOL-BASED ANTISEPTIC SOLUTIONS AGAINST GRAM NEGATIVE BACTERIA - Laura Wihanto; Handi Suyono (JURNAL WIDYA MEDIKA, 2021)
Introduction : Gram-negative bacteria infections cause diseases namely skin infection until sepsis including nosocomial infection. Prevention by antiseptic application is the way to inhibit infection. Some antiseptic compounds that have been used show resistance according to some reports. Aim: Determine the efficacy of ethanol-based antiseptic solutions against Gram-negative bacteria Methods : Discs saturated with ethanol-based antiseptic solutions were affixed to Muller Hinton agar which had been smeared by Acinetobacter baumannii ATCC BAA-747, Pseudomonas aeruginosa ATCC 27853, Klebsiella pneumonia ATCC BAA-1706, Escherichia coli ATCC 25922, Salmonella sp. , and Proteus vulgaris ATCC 6380. The diameter of the inhibition zone was read after 24 hours. Solutions are considered sensitive if the zone of inhibition of growth diameter is more than 6 millimeters (Kirby-Bauer disc diffusion method). Result : Acinetobacter baumannii and Salmonella sp is sensitive to solution consisting of ethanol 80 % and ethanol 80 %+ H2O2 0,15% . Pseudomonas aeruginosa and Eschericia coli is sensitive only to solution consisting of ethanol 80 %+ H2O2 0,15% As for Klebsiella pneumonia and Proteus vulgaris, they are resistance to both solutions. Conclusion: The use of ethanol-based antiseptic solutions with or without H2O2 0.15% addition may not effectively eliminate all gram-negative bacteria from the environment. The addition of 0.15% H2O2 to the antiseptic solution showed a better barrier effect than the solution containing only 80% ethanol. Adding other additives needs to be investigated further to formulate a better antiseptic solution against Gram-negative bacteria.